Stapled Haemorrhoidopexy in the Treatment of Haemorrhoidal Disease: A Prospective Study (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Background: Haemorrhoids are usually managed by open haemorrhoidectomy which is associated with postoperative pain, prolong hospital stay, longer convalescence and late return to normal activities. Stapled haemorrhoidopexy is a newer alternative for the treatment of haemorrhoid. The present study was designed to evaluate this technique in terms of duration of surgery & hospital stay, complications, convalescence, time return to normal activities, cost effectiveness and patient’s satisfaction.Materials and methods: One hundred and sixty patients of either sex who fulfilled the criteria were included in this study. More than 90% of the patients were in grade 3 & 4. All data were prospectively collected and examined. The patients were evaluated in terms of demographic properties, complaints on admission and postoperative complication.Results: 69.4% were male and 30.6% were female. Mean age was 40.93 years. Grade 3 haemorrhoid was present in 73.75% cases, Grade 4 was 18.12% cases, Grade 1 and Grade 2 were in 8.13% cases. The mean duration of surgery was 30 minutes. The mean duration of hospitalization was 36 hours. Intraoperative bleeding was observed in 9.38% patients. Reactionary haemorrhage was seen in 3.75% patients. Postoperative mild pain in 3.12% patients and residual prolapse in 1.25% cases.Conclusion: Stapled haemorrhoidopexy is safer alternative to open haemorrhoidotectomy with many short and long term benefits.J Bangladesh Coll Phys Surg 2020; 38(3): 126-134